Endurance time, muscular activity and the hand/arm tremor for different exertion forces of holding. Issue 1 (2nd January 2016) - Lee, Tzu-Hsien
Abstract : This study aimed to examine the effects of exertion force on endurance time, muscular activity and hand/arm tremor during holding. Fifteen healthy young males were recruited as participants. The independent variable was exertion force (20%, 40%, 60% and 80% maximum holding capacity). The dependent variables were endurance time, muscular activity and hand/arm tremor. The results showed that endurance time decreased with exertion force while muscular activity and hand/arm tremor increased with exertion force. Hand/arm tremor increased with holding time. Endurance time of 40%, 60% and 80% maximum holding capacity was approximately 22.7%, 12.0% and 5.6% of that of 20% maximum holding capacity, respectively. The rms (root mean square) acceleration of hand/arm tremor of the final phase of holding was 2.27-, 1.33-, 1.20- and 1.73-fold of that of the initial phase of holding for 20%, 40%, 60% and 80% maximum holding capacity, respectively.